GAMBARAN HISTOPATOLOGIS HATI TIKUS (Rattus novergicus) YANG DIINFEKSI Trypanosoma evansi SETELAH PEMBERIAN EKSTRAK KULIT BATANG JALOH (Salix tetrasperma Roxb) (Histopathological Changes of Rat (Rattus novergicus) Liver Infected with Trypanosoma evansi and Treated with Willow Tree Bark Extract (Salix tetrasperma Roxb)) - Mulya Fahmi; Yudha Fahrimal; Dwinna Aliza; Siti Aisyah; Hamdani Budiman; Muhammad Hambal (Jurnal Medika Veterinaria, 2015)
This research aimed to determine the effect of willow (Salix tetrasperma Roxb) tree bark extract on histopathological changes of liver of rat (Rattus novergicus) infected with Trypanosoma evansi. Liver of 25 male rat, Wistar strain, were used in this study and all rat were fed with commercial feed ad libitum. This research used completely randomized design (CRD) with 5 treatments, each treatment consisted of 5 replicates. Treatment I was negative control group without any treatment, treatment II were only infected with 103 T. evansi, treatment III, IV, and V were infected with 103 T. evansi and treated with willow tree bark extract with the dose of 30, 45, and 60 mg/kg bw, respectively. The administration of willow tree bark extract was carried out for 3 consecutive days orally using a stomach tube. All rats were sacrificed and necropsied then liver were collected for histopathological examination. Percentage of histophatological changes found in hepatocytes of rat infected with T. evansi after the administration of willow tree bark extract in group P1, P2, P3, P4, and P5 were: normal hepatocytes 96.28%; 0.00%; 8.06%; 40.61%; and 0.00%; hydropic degeneration 0.00%, 44.98%, 58.00%, 38.29%, and 35.04%; fatty degeneration 0.00%, 0.00%, 0.00%, 0.00%, and 8.76%; necrosis 3.72%, 55.02%, 33.94%, 21.10%, and 56.20, respectively. In conclusion, the administration of willow tree bark extract is able to protect rat’s liver from T. evansi infection and the dose of 45 mg/kg bw is more effective than 30 mg/kg bw but the dose of 60 mg/kg bw of willow tree bark extract worsen the liver damage.Key words: histopathology, liver, T. evansi, willow